G. Eyal, I. Szelenyi, E. Townsley, Capitalism fără capitaliști. Noua elită conducătoare din Europa de Est, București, Editura Omega, 2001 - Popa, Ioana Daniela (Calitatea Vieții, 2002)
Without abstract